ANALISIS PERKEMBANGAN ARTIFICIAL INTELLIGENCE DAN DAMPAKNYA TERHADAP PENCIPTAAN KARYA SENI DIGITAL DI ERA MODERN - Vicinsky Owen Tanner; Niko Ananda Limanto; Darriel Dapples; Dorie P. Kesuma (Jurnal Riset Sistem Informasi, 2026)
The development of Artificial Intelligence in the modern era has brought significant impacts across various fields, including the creation of digital artworks. This study aims to analyze the development of Artificial Intelligence in the world of digital art, its role in the creative process, its impact on artists’ creativity, as well as the challenges and problems arising from its use. The research method used is a qualitative method with a literature study approach through collecting data from scientific journals, articles, and other reliable sources. The results of the study show that Artificial Intelligence is able to assist the process of creating digital artworks by improving efficiency, productivity, and creative exploration. In addition to providing positive impacts, the use of Artificial Intelligence also creates negative impacts such as reducing the originality of artworks, diminishing emotional elements in art, and the potential replacement of human artists. Furthermore, the use of Artificial Intelligence in digital art also raises ethical and copyright issues related to ownership of works and the use of data as training material for Artificial Intelligence. Therefore, a balance between the utilization of Artificial Intelligence technology and human creativity is needed in order to maintain the aesthetic value and meaning of art.